Influence of ambient temperature in the city of Portoviejo, Ecuador on the energy performance of photovoltaic modules - Genial Belvinel Epeni-Tombo; María Rodríguez-Gámez; Guillermo A. Loor-Castillo; Antonio Vázquez Pérez; José Ricardo Nuñez Alvarez (International Journal of Electrical and Computer Engineering (IJECE), 2023)
The research analyzes the influence of the average temperature on the performance of specific photovoltaic solar modules under the environmental conditions of the city of Portoviejo, province of Manabí, Ecuador. The research is carried out using the qualitative methodology. Its main objective is to determine the influence of temperature on the energy performance of photovoltaic modules under the region's environmental conditions. Two electrical diagrams with different configurations were designed, which were analyzed and simulated using the MATLAB Simulink software. The results obtained show the direct relationship between the electrical parameters of voltage, current intensity, and power with the temperature value on the surface of the modules. It is concluded that the modules generate a higher value of voltage, electric current intensity, and electric power at a lower temperature, regardless of the level of solar irradiation they receive.